2015
DOI: 10.1177/0301006615596902
|View full text |Cite
|
Sign up to set email alerts
|

The Mirrored Hand Illusion: I Control, So I Possess?

Abstract: Certain situations may not only cause people to misjudge external information but also distort people's perception of themselves. The present study is the first to report the mirrored hand illusion which could be generated when the experimenter imitated the fist-clenching movements of the subject synchronously. The subjects formed the illusion that the experimenter's hand was "something I can control" when being imitated synchronously. In addition, a sense of ownership over the alien hand was established by in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
2
3
2
Order By: Relevance
“…The elicitation of agency is consistent with that reported in previous work, including the study of personperson interactions by Zhou et al 9 and studies of human-rubber hand interactions [6][7][8] (Table 1). In the humanrubber hand interactions, researchers have found that the synchronous movements of a rubber hand, placed congruently with a participant's hand, elicited a sense of agency in the participant [4][5][6][7][8] , and that a sense of agency was elicited when the participant was interacting but viewing the synchronous movements of a 180° rotated rubber hand in mirror-and non-mirror-symmetrical ways, as if it was another person's right or left hand [6][7][8] ( Table 1).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The elicitation of agency is consistent with that reported in previous work, including the study of personperson interactions by Zhou et al 9 and studies of human-rubber hand interactions [6][7][8] (Table 1). In the humanrubber hand interactions, researchers have found that the synchronous movements of a rubber hand, placed congruently with a participant's hand, elicited a sense of agency in the participant [4][5][6][7][8] , and that a sense of agency was elicited when the participant was interacting but viewing the synchronous movements of a 180° rotated rubber hand in mirror-and non-mirror-symmetrical ways, as if it was another person's right or left hand [6][7][8] ( Table 1).…”
Section: Discussionsupporting
confidence: 90%
“…This is because 0 means 'uncertain' on the seven-point Likert scale (−3 = totally disagree, 0 = uncertain, +3 = totally agree). This kind of uncertainty seemed consistent with participants' sense of hand location in Zhou et al 9 , in which the median of the shifted hand position (i.e., 3.32) was slightly below the uncertain level (i.e., 4).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In particular, researchers are exploring the effects of mindfulness-based practices on the formation, development and correction of self-consciousness in health and mental disorders. The legality of the use of correction programmes is based on mindfulness-based techniques as additional methods of various mental disorders treatment (including anxiety, depression, substance use disorders and other mental impairments, accompanied by selfconsciousness disorders) (Hazif-Thomas, Stephan, Walter, & Thomas, 2015;Fuente, 2016;Zhou, Zhang, Yin, & Yang, 2015;Berezovskaya, & Tichonova, 2012). There is an increase of awareness of negative thoughts and feelings in the process of using such programmes.…”
Section: State Of the Problemmentioning
confidence: 99%